Analysis of Mathematics Education Students’ Intitial Operational Research Skills - Dinar Nirmalasari; Fanisa Dina Amalia Dewi Umbara; Avianti Permata Yuniar (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2026)
Students' initial ability to understand Operational Research courses is important as a foundation for exploring more complex optimisation concepts. This study aims to describe the initial skills of Mathematics Education students and reveal their perceptions of Operations Research courses. The research method used is quantitative descriptive, with subjects being third-semester Mathematics Education Study Programme students. Data were collected through diagnostic tests in the form of essay questions to measure cognitive aspects and perception questionnaires to explore affective elements. Data analysis was conducted descriptively by calculating the average score, ability categories, and students' attitude tendencies. The results showed that students' initial abilities in Operations Research were still limited, particularly in mathematical model formulation and understanding of duality concepts. Students were relatively more capable of visualization and procedural skills but did not yet demonstrate adequate mastery of modelling that required conceptual abstraction. From an affective perspective, students have a positive perception of the usefulness of Operations Research, a high level of interest in learning it, and confidence in their abilities. However, there are also concerns about the material's difficulty level, especially on complex topics. These findings confirm that the success of Operations Research learning is influenced by a combination of students' cognitive and affective aspects. Therefore, learning strategies that emphasize strengthening modelling skills, applying problem-based learning, and integrating supporting technology to reduce the burden of manual computation are needed. With this approach, students are expected to be better prepared to handle material requiring high-level thinking skills.